Antibacterial Activity of Peucedanum ruthenicum, Johreniopsisseseloidesand Cervaria cervariifoliaExtracts: Antibacterial activity of plant extracts - Noor Sabri; Narguess Yassa; Ladan Salimi; Azadeh Manayi; Zahra Tofighi; Mohammad Reza Fazeli; Seyed Hamid Reza Alavi; Fatemeh Fouladi (Iranian Journal of Pharmaceutical Sciences, 2009)
Antimicrobial activity of the polar and nonpolar extracts of the roots and aerial parts of Peucedanum ruthenicumM. Bieb., Johreniopsis seseloides (C. A. Mey.)Pimenov and Cervaria cervariifolia(C. A. Mey.) Pimenov were examined against gram-positive and gram-negative bacteria. The polar extracts of the roots and aerial parts displayed no activity against bacteria, while the nonoplar extracts of the roots which contains coumarins, presented activity againstStaphylococcus aureus, S.epidermidis, Pseudomonas aeruginosaand Escherichia coli.